Risk Management Implementation of Conventional Bank Profitability Using the Ceo's Power as a Moderator Variable During the Covid-19 Pandemic - Sasongko, Seno; Aisyah F. Pulungan, Nur (Journal of World Science, 2023)
This study aims to examine the effect of risk management implementation on profitability of conventional commercial banks with CEO tenure as moderator variable during the covid-19 pandemic. This research is included in the hypothesis testing study. All banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2021 period are the population in this research. The sampling method was carried out by purposive sampling. F-count obtained the number 128.114 with a probability number of 0,000. This probability number is less than 0.05, so it can be said that the model is fit or appropriate and can be used to estimate profitability; in other words, it can be stated that NPL, NIM, LDR, BOPO, CEOTENURE *NPL, CEOTENURE*NIM, CEOTENURE*LDR, CEOTENURE*BOPO together -same effect simultaneously on profitability (ROA). NPL has a positive effect and its value is not significant to the ROA of conventional commercial banks. NIM has a positive influence and a significant value on the ROA of conventional commercial banks. LDR has a negative and insignificant effect on the ROA of conventional commercial banks. BOPO has a negative and significant impact on conventional commercial bank ROA. CEO Tenure cannot moderator the effect of NPL on the ROA of conventional commercial banks. CEO Tenure can moderator NIM's influence on conventional commercial banks' ROA. CEO Tenure cannot moderator LDR's effect on conventional commercial banks' ROA. CEO Tenure can moderator the influence of BOPO on the ROA of conventional commercial banks.